RELIGION COMMODITIZATION IN ADVERTISEMENT : SEMIOTIC ANALYSIS OF ZOYA VEIL ADVERTISEMENT IN INSTAGRAM - Istiqomah, Nurul; Noor Rakhmad, M.I.Kom, Drs. Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
This research starts from phenomenon of Zoya, the company uploaded advertising about halal certified veil in their official Instagram account on February 2016. The purpose of this study is to reveal the myth of halal symbols in the Zoya veil ads which certified halal. This study used a qualitative approach with a version of Roland Barthes semiotic analysis through the analysis stage denotation and connotation. Through these stages at the level of denotation, sign was analyzed both verbally and non-verbally, then at the level of connotative, sign was classified in the linguistic message, which was encoded iconic message, and the message was not encoded iconic. The results of this study indicate that the halal symbol in this ad contains a mythical value of goodness and blessing that consumers will get more than the usual veil or headscarf from other brands who did not use the halal label. Halal symbol in this ad can be said contain commoditization, assuming the manufacturer has changed used value into exchange economic value. The purpose of manufacturers uses halal symbol on its products leads to consumerism, the manufacturer wants to earn the trust of Muslim consumers that are attached to the halal symbol, and ends on the consumer's decision to purchase the product Zoya.